Intra-Subject Variability and Diurnal Cycle of Ocular Perfusion Pressure as Characterized by Continuous Telemetry in Nonhuman Primates - Wilson, Katherine I.; Godara, Pooja; Jasien, Jessica V.; Zohner, Emma; Morris, Jeffrey S.; Girkin, Christopher A.; Samuels, Brian C.; Downs, J. Crawford (Investigative ophthalmology & visual science, 2020)
To characterize ocular perfusion pressure (OPP) fluctuations with continuous telemetry over 24-hour periods across multiple days in nonhuman primates (NHPs) to test the hypotheses that OPP differs among NHPs and that the diurnal cycle of OPP is characterized by low OPP during sleep. We have developed and validated two implantable radiotelemetry systems that allow continuous measurement of intraocular pressure (IOP), arterial blood pressure (BP), and OPP up to 500 Hz. OPP was measured unilaterally in 12 male NHPs for periods of 38 to 412 days. IOP transducers were calibrated directly via anterior chamber manometry, and OPP was calculated continuously as central retinal artery BP minus IOP. OPP data were corrected for signal drift between calibrations and averaged hourly. OPP varied widely among animals, with daily averages ranging from ∼47 to 65 mm Hg. In eight of 12 NHPs, OPP was significantly lower during sleep compared to waking hours. In three animals, the diurnal cycle was reversed and OPP was significantly higher during sleep (P < 0.05), and one NHP showed no diurnal cycle. Day-to-day OPP variability within NHPs was the largest source of overall OPP variability, even larger than the differences between NHPs. Average daily OPP showed an unexplained ∼32-day cyclic pattern in most NHPs. Average OPP varied widely and exhibited differing diurnal cycles in NHPs, a finding that matches those of prior patient studies and indicates that OPP studies in the NHP model are appropriate. Infrequent snapshot measurements of either IOP or BP are insufficient to capture true IOP, BP, and OPP and their fluctuations.